2013
DOI: 10.1016/j.csm.2012.08.006
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Anterior Cruciate Ligament Reconstruction on In Vivo, Dynamic Knee Function

Abstract: Synopsis The purposes of this article are to discuss key factors for assessing joint function, to present some recent findings and to address the future directions for evaluating the function of the ACL-injured/reconstructed knees. Well-designed studies, using state-of-the art tools to assess knee kinematics under in vivo, dynamic, high-loading conditions, are necessary to evaluate the relative performance of different procedures for restoring normal joint motion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 66 publications
0
24
0
Order By: Relevance
“…Moreover, surgical reconstruction of the ACL may not completely restore the injury‐induced anterior tibial translation, providing more evidence for a shift in kinematic gait following reconstruction; such an anterior shift may place more load on the patellar cartilage . In the injured knee, reevaluations of surgical procedures have been made in response to this evidence of insufficient restoration of joint kinematics …”
Section: Discussionmentioning
confidence: 99%
“…Moreover, surgical reconstruction of the ACL may not completely restore the injury‐induced anterior tibial translation, providing more evidence for a shift in kinematic gait following reconstruction; such an anterior shift may place more load on the patellar cartilage . In the injured knee, reevaluations of surgical procedures have been made in response to this evidence of insufficient restoration of joint kinematics …”
Section: Discussionmentioning
confidence: 99%
“…Abnormal knee motion is believed to be an important factor contributing to the development of OA after ACL reconstruction (Gao et al, 2012; Papannagari et al, 2006; Tashman and Araki, 2013; Tashman et al, 2004). Specifically, recent studies have theorized that abnormal knee motion alters cartilage stress and strain distributions, thus initiating a cascade of degenerative changes (Andriacchi et al, 2004; DeFrate et al, 2006; Li et al, 2006; Tashman et al, 2007; Tochigi et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Although a number of factors potentially contribute to the development of osteoarthritis after ACL injury, altered joint motion is believed to be one important factor (Andriacchi et al, 2004; Chen et al, 2012; Papannagari et al, 2006; Tashman and Araki, 2013; Tochigi et al, 2011). In particular, recent studies have suggested that some ACL reconstruction techniques may not restore normal tibiofemoral joint motions under physiological loading conditions (Abebe et al, 2011b; Gao and Zheng, 2010; Papannagari et al, 2006; Tashman and Araki, 2013). These abnormal joint motions are believed to alter normal cartilage contact mechanics (Andriacchi et al, 2004; Hosseini et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…[98] Dual fluoroscopy and dynamic stereo-radiography is becoming more widely accessible because it provides better precision and more reliability than the use of high-speed cameras or marker based motion capture systems. [98] Hoshino and colleagues[99] investigated whether knee kinematics and joint contact mechanics can be restored after ACLR with a double-bundle or single-bundle graft using dynamic stereo x-ray to capture biplane radiographic images. The athletes were on average a little more than one year out from ACLR and were performing downhill treadmill running.…”
Section: Functional Recovery Of the Kneementioning
confidence: 99%
“…[112] Current techniques in ACLR over the past several years have focused on reproducing more anatomical tunnel placement and graft geometry to restore knee kinematics. [98] Xu et al[113] demonstrated in a cadaveric study that an anatomic anteromedial tunnel placement can lead to biomechanical advantages when compared to a non-anatomic placement, and the anatomic placement better restores knee kinematics to the native intact ACL state. [113] However, the anatomic placement had significantly greater in situ forces than the non-anatomic placement making it more vulnerable to graft failure.…”
Section: Functional Recovery Of the Kneementioning
confidence: 99%